Cluster-derived Gold/Iron catalysts for environmental applications - Bonelli, Rosa <1982> (Alma Mater Studiorum - Università di Bologna, 2010)
During the last years we assisted to an exponential growth of scientific discoveries for catalysis by gold and many applications have been found for Au-based catalysts. In the literature there are several studies concerning the use of gold-based catalysts for environmental applications and good results are reported for the catalytic combustion of different volatile organic compounds (VOCs). Recently it has also been established that gold-based catalysts are potentially capable of being effectively employed in fuel cells in order to remove CO traces by preferential CO oxidation in H2-rich streams. Bi-metallic catalysts have attracted increasing attention because of their markedly different properties from either of the costituent metals, and above all their enhanced catalytic activity, selectivity and stability. In the literature there are several studies demostrating the beneficial effect due to the addition of an iron component to gold supported catalysts in terms of enhanced activity, selectivity, resistence to deactivation and prolonged lifetime of the catalyst. In this work we tried to develop a methodology for the preparation of iron stabilized gold nanoparticles with controlled size and composition, particularly in terms of obtaining an intimate contact between different phases, since it is well known that the catalytic behaviour of multi-component supported catalysts is strongly influenced by the size of the metal particles and by their reciprocal interaction. Ligand stabilized metal clusters, with nanometric dimensions, are possible precursors for the preparation of catalytically active nanoparticles with controlled dimensions and compositions. Among these, metal carbonyl clusters are quite attractive, since they can be prepared with several different sizes and compositions and, moreover, they are decomposed under very mild conditions. A novel preparation method was developed during this thesis for the preparation of iron and gold/iron supported catalysts using bi-metallic carbonyl clusters as precursors of highly dispersed nanoparticles over TiO2 and CeO2, which are widely considered two of the most suitable supports for gold nanoparticles. Au/FeOx catalysts were prepared by employing the bi-metallic carbonyl cluster salts [NEt4]4[Au4Fe4(CO)16] (Fe/Au=1) and [NEt4][AuFe4(CO)16] (Fe/Au=4), and for comparison FeOx samples were prepared by employing the homometallic [NEt4][HFe3(CO)11] cluster. These clusters were prepared by Prof. Longoni research group (Department of Physical and Inorganic Chemistry- University of Bologna). Particular attention was dedicated to the optimization of a suitable thermal treatment in order to achieve, apart from a good Au and Fe metal dispersion, also the formation of appropriate species with good catalytic properties. A deep IR study was carried out in order to understand the physical interaction between clusters and different supports and detect the occurrence of chemical reactions between them at any stage of the preparation. The characterization by BET, XRD, TEM, H2-TPR, ICP-AES and XPS was performed in order to investigate the catalysts properties, whit particular attention to the interaction between Au and Fe and its influence on the catalytic activity. This novel preparation method resulted in small gold metallic nanoparticles surrounded by highly dispersed iron oxide species, essentially in an amorphous phase, on both TiO2 and CeO2. The results presented in this thesis confirmed that FeOx species can stabilize small Au particles, since keeping costant the gold content but introducing a higher iron amount a higher metal dispersion was achieved. Partial encapsulation of gold atoms by iron species was observed since the Au/Fe surface ratio was found much lower than bulk ratio and a strong interaction between gold and oxide species, both of iron oxide and supports, was achieved. The prepared catalysts were tested in the total oxidation of VOCs, using toluene and methanol as probe molecules for aromatics and alchols, respectively, and in the PROX reaction. Different performances were observed on titania and ceria catalysts, on both toluene and methanol combustion. Toluene combustion on titania catalyst was found to be enhanced increasing iron loading while a moderate effect on FeOx-Ti activity was achieved by Au addition. In this case toluene combustion was improved due to a higher oxygen mobility depending on enhanced oxygen activation by FeOx and Au/FeOx dispersed on titania. On the contrary ceria activity was strongly decreased in the presence of FeOx, while the introduction of gold was found to moderate the detrimental effect of iron species. In fact, excellent ceria performances are due to its ability to adsorb toluene and O2. Since toluene activation is the determining factor for its oxidation, the partial coverage of ceria sites, responsible of toluene adsorption, by FeOx species finely dispersed on the surface resulted in worse efficiency in toluene combustion. Better results were obtained for both ceria and titania catalysts on methanol total oxidation. In this case, the performances achieved on differently supported catalysts indicate that the oxygen mobility is the determining factor in this reaction. The introduction of gold on both TiO2 and CeO2 catalysts, lead to a higher oxygen mobility due to the weakening of both Fe-O and Ce-O bonds and consequently to enhanced methanol combustion. The catalytic activity was found to strongly depend on oxygen mobility and followed the same trend observed for catalysts reducibility. Regarding CO PROX reaction, it was observed that Au/FeOx titania catalysts are less active than ceria ones, due to the lower reducibility of titania compared to ceria. In fact the availability of lattice oxygen involved in PROX reaction is much higher in the latter catalysts. However, the CO PROX performances observed for ceria catalysts are not really high compared to data reported in literature, probably due to the very low Au/Fe surface ratio achieved with this preparation method. CO preferential oxidation was found to strongly depend on Au particle size but also on surface oxygen reducibility, depending on the different oxide species which can be formed using different thermal treatment conditions or varying the iron loading over the support.